Survei Kepuasan Masyarakat pada Program Satya Gawa dari PT. Indonesia Power Suralaya PGU - Kandung Sapto Nugroho; Agus Sjafari; Luthfie Masyhadi (UIR Press, 2023)
This article surveys the implementation of the Satya Gawa Program as part of the social responsibility of PT Indonesia Power Suralaya PGU. This program is intended for people with psychiatric problems, both patients and their families with the aim of improving mental health. The purpose of this study is to determine the success of the implementation of the Mental Disorder Service Center (Satya Gawa). The method used is a survey of patients and families of patients with mental disorders (ODGJ) on the aspect of existence of community development officers, community involvement in planning, implementation and evaluation, conformity with user needs, relevance to cultural, social and economic values, ability to improve knowledge, skills and improving the welfare of the target group. The results of the study show positive performance, meaning that it does not require major changes to the program, but requires minor changes in efforts to involve participation in planning and evaluation, use of opportunities to express opinions, increase income, and continue the Satya Gawa Program.